2013
DOI: 10.1210/jc.2013-2531
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol, Aspirin, and Indomethacin Induce Endocrine Disturbances in the Human Fetal Testis Capable of Interfering With Testicular Descent

Abstract: Analgesics at concentrations relevant to human exposure cause endocrine disturbances in the fetal testis. We suggest that the fetal human testis displays slight critical age windows for sensitivity to direct exposure to aspirin, indomethacin, and paracetamol. The analgesic-induced inhibition of INSL3 may be the mechanism by which analgesics increase the risk of cryptorchidism. Greater caution is required concerning consumption of analgesics during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
3
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 46 publications
9
118
3
2
Order By: Relevance
“…The interindividual variations in the levels of INSL3, the other Leydig cell hormone investigated, were greater than those of testosterone, as generally observed (Ivell et al, 2013;Mazaud-Guittot et al, 2013). This and the NMDR also often encountered with this hormone complicated the interpretation of our data.…”
Section: Inhibin Bmentioning
confidence: 49%
“…The interindividual variations in the levels of INSL3, the other Leydig cell hormone investigated, were greater than those of testosterone, as generally observed (Ivell et al, 2013;Mazaud-Guittot et al, 2013). This and the NMDR also often encountered with this hormone complicated the interpretation of our data.…”
Section: Inhibin Bmentioning
confidence: 49%
“…It may be due to male germ-line epigenetic effects as described in endocrine disruption effects of acetaminophen on the human testis. 15,16 At least 3 plausible hypotheses are proposed to explain the association between maternal acetaminophen use and ADHD. First, neonatal exposure to acetaminophen changes the levels of brain-derived neurotropic factor in mice and results in altered behavior, lowered fear responses, and reduced learning abilities in adulthood.…”
Section: Figurementioning
confidence: 99%
“…However, acetaminophen and endocrine disruptors have been shown to have potential for transgenerational disease transmission effects in mouse models via male germ-line epigenetic effects, and endocrine disruption effects of acetaminophen have been shown in the human testis. 15,16 It is therefore important to estimate the effect of paternal prepregnancy use.…”
mentioning
confidence: 99%
“…Although the exposure levels were chosen based on the estimated serum concentrations as that occurring after therapeutic use, the resulting testicular concentrations in adult men are unknown and rather difficult to determine. Mazaud-Guittot et al (2013) used an in vitro system based on the cell culture of human fetal testes exposed to NA4AP and its metabolite N-arachinodyl-4-phenolamine (AM404; see 'Metabolism of R108 H Modick and others acetaminophen and aniline' section) and other NSAIDs at concentrations ranging from 10 K4 to 10 K7 M. Endocrine-disrupting properties were investigated through measures of testosterone, anti-Mü llerian hormone (AMH), insulin-like factor 3 (INSL3), and PGs (PGD2 and PGE2) (Mazaud-Guittot et al 2013). The authors found significant inhibition of INSL3 production in samples exposed to NA4AP and AM404, with a significant dose-response relationship indicating a decrease in INSL3 production with an increasing dose of NA4AP.…”
Section: K5mentioning
confidence: 99%